2013
DOI: 10.1111/1744-7917.12060
|View full text |Cite
|
Sign up to set email alerts
|

Use of a dietary exposure system for screening of insecticidal compounds for their toxicity to the planthopper Laodelphax striatellus

Abstract: We developed a dietary exposure assay for screening insecticidal compounds for their toxicity and for assessing the side effects of insecticidal proteins produced by genetically engineered (GE) plants on the planthopper Laodelphax striatellus Fallén. The fitness bioassay confirmed that the diet fulfills the requirements to be used in the dietary exposure system. To validate the efficacy of the dietary exposure system, nymphs of L. striatellus were fed diets treated with different concentrations of an inorganic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Larvae and adults of the green lacewing, C. sinica , were not affected by feeding on Cry1C or Cry2A proteins or on Cry1C- or Cry2A-containing Bt rice pollen 10 11 12 36 . The planthopper, Laodelphax striatellus (Homoptera: Delphacidae), was not adversely affected when fed an artificial diet containing Cry2A at 300 μg/g diet 37 . Larvae of the silkworm, B. mori , were fed Cry1C- or Cry2A rice pollen 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Larvae and adults of the green lacewing, C. sinica , were not affected by feeding on Cry1C or Cry2A proteins or on Cry1C- or Cry2A-containing Bt rice pollen 10 11 12 36 . The planthopper, Laodelphax striatellus (Homoptera: Delphacidae), was not adversely affected when fed an artificial diet containing Cry2A at 300 μg/g diet 37 . Larvae of the silkworm, B. mori , were fed Cry1C- or Cry2A rice pollen 13 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yang et al showed that Bt rice (T1C‐19 or T2A‐1) did not affect the ecological fitness parameters, including nymphal survival rate and duration, sex ratio and female adult weight, and nor the detoxification enzyme activities of BPH compared with non‐ Bt rice (MH63); however, the key parameters for population growth, namely the fecundity and population dynamics in the field, were not evaluated. In addition, an artificial diet study with the small brown planthopper, Laodelphax striatellus Fallén (Hemiptera: Delphacidae), has revealed no sensitivity to high doses of purified Cry2Aa …”
Section: Introductionmentioning
confidence: 99%
“…Each treatment was repeated three times. Using the method reported by Liu et al, 18 the insecticidal activity of the protein against three hemipteran pests was determined with a double parafilm membrane feeding system. Twenty-one individuals were used on one replication.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%